Effect of Serum Leptin on Weight Gain Induced by Olanzapine in Female Patients with Schizophrenia - Tsuneyama, Nobuto (PLoS One, 2016)
BACKGROUND: Olanzapine (OLZ) treatment is associated with a high risk of weight gain, and may cause abnormalities in glycolipid metabolism. Therefore, the underlying mechanism of OLZ-related weight gain is needed to clarify but not yet been adequately determined. In recent years, adipocytokines such as leptin, adiponectin, and tumor necrosis factor (TNF)-α, which play important roles in energy homeostasis, have been suggested as biomarkers of weight gain. Here, we determined if baseline plasma concentrations of leptin, adiponectin, and TNF-α predict weight gain following OLZ treatment. METHODS: We recruited 31 schizophrenia outpatients (12 men and 19 women, 28.8 ± 10.2 years old) that were unmedicated or on another antipsychotic monotherapy medication. Baseline body mass index (BMI) and plasma levels of leptin, adiponectin, and TNF-α were obtained. All patients started or were switched to OLZ monotherapy for a maximum of 1 year. BMI was also obtained at the endpoint. RESULTS: Mean BMI change following OLZ treatment was 2.1 ± 2.7 kg/m(2). BMI change from baseline to endpoint negatively-correlated with baseline leptin levels in female patients (r = −0.514, P = 0.024), but not male patients. Baseline adiponectin or TNF-α levels were not correlated with BMI change. CONCLUSION: Baseline plasma leptin can have an effect on subsequent weight gain following OLZ treatment in female patients with schizophrenia.